2012
DOI: 10.1039/c2lc40059f
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage electroosmotic pumps fabricated from track-etched polymer membranes

Abstract: Track-etched polymer membranes are used to realize low-voltage electroosmotic (EO) pumps. The nanopores in polycarbonate (PC) and polyethylene terephthalate (PET) membranes were fabricated by the track-etching technique, the pore diameter was controlled in the range of 100 to 250 nm by adjusting the etching time. The results show that these EO pumps can provide high flow rates at low applied voltages (2-5 V). The maximum normalized flow rate is as high as 0.12 ml min(-1) V(-1) cm(-2), which is comparable to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…6. We measured a maximum limiting hydrostatic pressure of 24.8 ± 1.8 mmH 2 O V −1 or 0.25 kPa V −1 , similar to what Wang et al reported, even though their membranes had approximately double the pore diameter (Wang et al 2012).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…6. We measured a maximum limiting hydrostatic pressure of 24.8 ± 1.8 mmH 2 O V −1 or 0.25 kPa V −1 , similar to what Wang et al reported, even though their membranes had approximately double the pore diameter (Wang et al 2012).…”
Section: Resultssupporting
confidence: 71%
“…Figure 5 shows the mass flux (calculated per unit membrane area) and the volumetric flow rate versus applied potential as well as the average of the current density measured for each applied potential. The maximum mass flux was measured to be 28 mg min −1 cm −2 , using 1 mM NaCl at 5 V. Similarly arranged measurements using other brands of track-etched polycarbonate membranes are reported to have flow rates (normalized by total cross-sectional pore area) up to 120 µl min −1 cm −2 per volt of applied potential, pumping deionized water (Kwon et al 2012;Wang et al 2012). For our membrane, we estimate a corresponding maximum normalized volumetric flow rate of 50 µl min −1 cm −2 per V of applied potential for 1 mM NaCl, pH 5.6, similar to that reported for a polycarbonate membrane in 1 mM borate buffer at pH 9 (Kwon et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The open capillary has the ability to deliver a wide range of sample reagents such as pure liquid drug reagents and aqueous solutions containing cells, particles, or biochemical macromolecules. The porous media EOF pumps [25][26][27][28][29][30][31][32] can also be used to drive pure liquid sample reagents for the injection purpose. For on-chip microfluidic delivery, open-channel EOF pumps [20][21][22][23][24] are the most popular pumping devices.…”
Section: Microfluidic Delivery and Actuationmentioning
confidence: 99%
“…Porous membrane EOF pumps [25][26][27][28] utilize a piece of porous membrane to construct submicroscale or nanoscale pump channels within. They are miniaturized and highly integrated microfluidic pumping devices.…”
Section: Porous Membrane Electroosmotic Flow (Eof) Pumpmentioning
confidence: 99%